Missing at Work - Sickness-related Absence and Subsequent Job Mobility - Adrian Chadi; Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Economists often interpret absenteeism as an indicator of effort. Using data from the German Socio-Economic Panel (SOEP) study, this paper offers a comprehensive discussion of this view by analysing various forms of job mobility. The evidence reveals a significantly negative (positive) link between sickness-related absence and the probability of a subsequent promotion (dismissal). In line with the interpretation of absenteeism as a proxy for effort, instrumental variable analyses suggest no causal impact of absence behaviour on the likelihood of such career events when variation in illness-related absence is triggered exogenously. We observe no consistent gender differences in the link between absence and subsequent career events.
Keywords: J22; J63; M51; 330